Żydowskie studiowanie Tory - Krajewski, Stanisław (Verbum Vitae, 2005)
Stanisław Krajewski, a believing Jew, co-director of the Polish Council of Christians and Jews, explains the most characteristic traits of Jewish studies and interpretation of the Torah. He eoneludes with the statement that the Torah, when it is studied, becomes a living organism which has an effect on those who read, meditate and take it seriously while going about their daily activities.